Simultaneous improvements in flammability and mechanical toughening of epoxy resins through nano-silica addition - Roenner,N; Hutheesing,K; Fergusson,A; Rein,G (Fire Safety Journal, 2017)
Polymers in transport, and many other engineering applications, are required to be mechanically tough as well as resistant to ignition and flame spread. These demands are often for many polymer types in competition, especially when adding flame retardants. With nano-silica addition, we show that improvements in both properties of a polymer can be achieved simultaneously. In this study, an epoxy resin is evaluated for its flammability and mechanical properties with step wise additions of nano-silica. The fracture toughness was significantly improved. In the single edge notch bending test, the addition of 36% nano-silica particles doubled the toughness and increased the flexure modulus by 50%. Flammability was studied via time to ignition at constant irradiation, and via a UL94 test coupled with mass loss and surface temperature measurements. Modelling for the heat transport and chemical kinetics in Gpyro was done and yielded good agreement with the temperatures measured. Adding up to 36% nano-silica, the time to ignition increased by 38% although a sharp decrease was observed around 24% SiO2 addition. We show that the increased time to ignition is mostly due to a higher thermal diffusivity, increased inert content, as well as a strengthening of the residue outer skin, which acts as a mass barrier for pyrolysate. This outer skin was analysed using a scanning electron microscope coupled with an energy dispersive X-ray spectrometer. We found that in the skin the nano-silica particles agglomerate at the surface forming a strong continuous structure together with the char residue from the epoxy. Improvements in the flammability as seen in the UL94 test were measured with mass loss showing a 30% reduction after 20 s, and surface temperatures at the ignited end being up to 75 K lower compared to the pure epoxy. Modelling in Gpyro supported the temperature measurements taken. Despite the improvements seen, all samples ignited, failing the test with dripping and showing that